Penguatan Digitalisasi Desa Wisata Ngreco Melalui Pemberdayaan Masyarakat Untuk Promosi Yang Efektif - Fatahillah, Rizqi Arohman; Firdaus, Ardhan Aulia; Aji, Prima Simpati; Berliana, Pepy Celi; Putri, , Elma Anindita; Dzakiyyah, Siti Asdilla; Fadhila, Dea Okwenty; Qonitah, Laili; Putra, Muhammad Raihan Dicka Pradita; Fadhilah, Teuku Muhammad Attar (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
This program aims to enhance the capacity of the Ngreco Village community in utilizing digital technology as a tourism promotion strategy through the implementation of village digitalization activities. The initiative was driven by the decline in tourist visits and the community's limited ability to effectively manage digital media. The methods used included observation, interviews, and Focus Group Discussions (FGDs) to identify community needs and design a targeted empowerment program. The program was carried out in three stages: socialization, seminars, and training, with a main focus on managing social media and digital platforms such as Instagram, TikTok, and Google My Business. The results showed a significant increase in participants' understanding and skills in creating promotional content and independently managing social media accounts. Active participation from the tourism awareness group (Pokdarwis) and village youth further strengthened the program's success. Additionally, the formation of the Village Digital Team became a strategic step to ensure the sustainability of digital promotion efforts. Although challenges remain—such as limited access to devices and internet infrastructure—the program has successfully contributed to broader and more efficient tourism promotion for Ngreco Village.